Análise numérica do comportamento térmico de lajes lisas protendidas submetidas a diferentes cenários de incêndio - Brackmann, Gabriela Dalfollo (2023)
The use of post-tensioned flat slabs in buildings is increasing due to several benefits that the system has, such as construction speed, reduction in the number of columns and increased free spans. Within the scope of the technical standards for the design of concrete structures in fire situations currently in force, their predominantly prescriptive character stands out. The regulations do not present a procedure for verifying structural safety in a fire situation and do not differentiate between bonded and unbonded prestressing, despite them exhibiting different behaviors at high temperatures. Furthermore, the prescriptions of ABNT NBR 15200 (2012) are based on the ISO 834 (1999) heating curve. However, when it comes to buildings with prestressed concrete elements, natural fires are more relevant. Computational modeling, using the Finite Element Method, has been widely used to study the behavior of structural elements in fire situations, as fire resistance tests have elevated costs and a series of executive difficulties. Therefore, the present work proposes to develop a numerical model to simulate the thermal behavior of post-tensioned concrete flat slabs subjected to different fire scenarios. Using the commercial program ABAQUS, three finite element models were developed: a concrete flat slab post-tensioned with bonded tendons, a concrete flat slab post-tensioned with unbonded tendons and a reinforced concrete flat slab. The models were validated with data available in the literature for the ISO 834 (1999) curve and for the hydrocarbon curve. After validating the models, parametric analysis were carried out, which consisted of simulating 18 natural fire curves, in which varied the duration of the heating phase and the cooling rate. In a second stage, the applicability of the prescriptions of ABNT NBR 15200 (2012) was verified when post-tensioned flat slabs are exposed to the hydrocarbon curve, simulating the exposure of the slab to the hydrocarbon curve for 240 minutes. From the results obtained, it was possible to conclude that the prescriptions of the Tabular Method of ABNT NBR 15200 (2012) regarding distance c1 are insufficient to limit the maximum temperature of prestressing tendons to 350°C during exposure to natural fires and the hydrocarbons curve. An equation to predict the maximum temperature of prestressing tendons positioned inside concrete flat slabs exposed to natural fires was obtained from parametric analysis data. The equation is a function of the duration of the heating phase and the cooling rate and was validated for cooling rates between 2 and 10 °C/min.